Antibacterial Activity of Oregano (Origanum vulgare L.) Essential Oil Vapors against Microbial Contaminants of Food-Contact Surfaces - Loris Pinto; Salvatore Cervellieri; Thomas Netti; Vincenzo Lippolis; Federico Baruzzi (MDPI AG, 2024)
The antimicrobial effect of eight essential oils' vapors against pathogens and spoilage bacteria was assayed. Oreganum vulgare L. essential oil (OVO) showed a broad antibacterial effect, with Minimum Inhibitory Concentration (MIC) values ranging from 94 to 754 µg cm−3 air, depending on the bacterial species. Then, gaseous OVO was used for the treatment of stainless steel, polypropylene, and glass surfaces contaminated with four bacterial pathogens at 6-7 log cfu coupon−1. No viable cells were found after OVO treatment on all food-contact surfaces contaminated with all pathogens, with the exception of Sta. aureus DSM 799 on the glass surface. The antimicrobial activity of OVO after the addition of beef extract as a soiling agent reduced the Sta. aureus DSM 799 viable cell count by more than 5 log cfu coupon−1 on polypropylene and glass, while no viable cells were found in the case of stainless steel. HS-GC-MS analysis of the headspace of the boxes used for the antibacterial assay revealed 14 different volatile compounds with α-Pinene (62-63%), and p-Cymene (21%) as the main terpenes. In conclusion, gaseous OVO could be used for the microbial decontamination of food-contact surfaces, although its efficacy needs to be evaluated since it depends on several parameters such as target microorganisms, food-contact material, temperature, time of contact, and relative humidity.